Lieder der Frauen und Mädchen in der slowakischen Volksmusik - Elschek, Oskár (Traditiones (Ljubljana), 1999)
The article is diveded into three chapters. The first deals with different opportunities on which songs became exclusively, or at least predominantly, the domain of woman. The second lists different reasons why song collectors had turned mainly to women - these have namely been proved the best preserversof tradition. The third chapter discusses the content, form and music characteristics of women's songs
Keywords: folk music; ljudska glasba; ljudske pesmi; Ethnopoetics; Slovaška